Curious George and the dump truck - Rey, Margret and H.A.; Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Vipah Interactive (Boston : Houghton Mifflin, 1999)
Curious George gets into trouble when he boards a dump truck and spills a load of dirt in a pond but redeems himself when the dirt creates an island for the pond$1 (Bs ducks.s
The 1984 edition of this title has a different story line.
Keywords: Monkeys -- Fiction; Dump trucks -- Fiction; Ducks -- Fiction